Pengaruh Filsafat Hukum Terhadap Dinamika Pembentukan Hukum Modern - Yuwono Prianto; Frangky Jonatan; Vinshen Saputra; Lena Mariana Br Sitorus (Dinasti Research, 2025)
Legal philosophy plays an important role in bridging the relationship between law, society, and changing times. Rooted in the principle of